THE EFFECTIVENESS OF THE SOCIO-SCIENTIFIC ISSUES BASED NUMBERED HEAD TOGETHER LEARNING MODEL ON STUDENT’S METACOGNITIONS ABILITY - Huriljannah, Maulida; Ekapti, Rahmi Faradisya (Science Education, Institut Agama Islam Negeri Ponorogo, 2024)
The low understanding of students in receiving learning materials makes the grades and achievements of these students tend to be lower, this is caused by several factors. As for one of the factors related to the understanding of students in receiving learning materials and the success of the learning process, especially science subjects, namely the metacognitive abilities of these students. To be able to attract students' interest in learning and also to be able to improve the metacognition abilities of students, especially in science subjects, a learning model is needed and accompanied by an appropriate and effective approach so that it can attract students' interest in learning and can also improve students' metacognition abilities. In conducting research, the type of research used is experimental quantitative research. The population in this study were seventh grade students at MTs Darul Huda Ponorogo, where the samples taken were students of class VII-32 totaling 24 students and class VII-33 totaling 25 students. This study used observation methods, response questionnaires, and metacognition tests as data collection instruments. Based on data analysis, it was found that the implementation of the learning process using the NHT (Numbered Head Together) model based on SSI (Socioscientific Issue) at MTs Darul Huda was very well implemented, students' responses to the learning process using the NHT (Numbered Head Together) model based on SSI (Socioscientific Issue) obtained 95% very good response, After conducting the N-Gain test to determine the effectiveness of the learning model applied by researchers, it can be seen that the use of the NHT (Numbered Head Together) method is quite effective in improving the metacognitive abilities of students in science subjects on environmental pollution material.